(untitled) (Studies of Transition States and Societies, 2024)
The year 2024 has been an intense one at STSS. The most important and shocking news is the passing away of our co-editor in chief, Professor Ellu Saar. Ellu served as a Professor of Sociology at the School of Governance, Law and Society (SOGOLAS) at Tallinn University since 2001 and was Senior Researcher at the IISS. She had been awarded the Estonian Research Prize in Social Sciences, and in 2022, was elected a member of the Estonian Academy of Sciences. Since 2012, she was elected as editor-in-chief of the sociological section of STSS and guided a number of authors to publish with us, importantly stirring sociological debates in Estonia and beyond. From 2015 to 2021, she was the head of the sociology programmes at TLU SOGOLAS, and from 2016 to 2023, she led the Centre of Excellence in Life Course Studies at TLU. It is with great sadness that we received the news on 2 June 2024. An obituary has been included at the end of this issue.